2022
DOI: 10.1038/s41598-022-13716-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds, antibacterial and antioxidant activities of methanol extract of Tamarindus indica Linn.

Abstract: Tamarindus indica is one of the tropical medicinal plants that has been attributed curative potential of numerous diseases by many rural dwellers. This study was designed to evaluate the antioxidant, antibacterial activities and also to determine the various chemical constituents responsible for its pharmacological activities. The methanol extract of Tamarindus indica fruit pulp was analyzed by Gas Chromatography/Mass Spectrometer to determine the volatile compounds present. The antioxidant activities were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…Similarly, a more recent study by Fagbemi et al [ 45 ] on bioactive compounds, antibacterial and antioxidant activities of methanol extract against Escherichia coli , Klebsiella pneumoniae , Pseudomonas aeruginosa , Acinetobacter calcaoceuticus , Plesiomonas shigelloides Bacillus cereus , and Staphylococcus aureus , also revealed the effectiveness of the extract on all the tested bacteria strains, and gave credit to the presence of β-sitosterol, cis-Vaccenic acid and other compounds like alkaloids and flavonoid as reported by other studies. The present study therefore, confirms previous findings and backs the evidence that suggests the involvement of fruit pulp in pharmaceutical products against pathogenic bacteria.…”
Section: Resultssupporting
confidence: 61%
“…Similarly, a more recent study by Fagbemi et al [ 45 ] on bioactive compounds, antibacterial and antioxidant activities of methanol extract against Escherichia coli , Klebsiella pneumoniae , Pseudomonas aeruginosa , Acinetobacter calcaoceuticus , Plesiomonas shigelloides Bacillus cereus , and Staphylococcus aureus , also revealed the effectiveness of the extract on all the tested bacteria strains, and gave credit to the presence of β-sitosterol, cis-Vaccenic acid and other compounds like alkaloids and flavonoid as reported by other studies. The present study therefore, confirms previous findings and backs the evidence that suggests the involvement of fruit pulp in pharmaceutical products against pathogenic bacteria.…”
Section: Resultssupporting
confidence: 61%
“…There were 37 compounds identified by the GC-MS analysis. Two of the bioactive substances were comparable to our research, including 5-Hydroxymethylfurfural (31.06%) and n-Hexadecanoic acid (1.38%), which have been reported to have anticancer activity, as well as a variety of prophylactic, antibacterial, antifungal, and antitubercular activities[42].…”
supporting
confidence: 84%
“…Table 3 represents the most important chemical compounds found in the water Yass extract, and the results were the best results extracted from the activity against bacteria (table 10), as this extract was able to reduce most of the bacterial activity. C6H6O3 has an area of 39.1388% It represents the highest recorded area, Phenol compounds are the most effective against bacteria, especially with accompanying C6H8O4 [23]. The study revealed that most phenolic compounds are present in water Yass, such as C3H6O3, and C6H6O2, these compounds have a high ability to oxidize.…”
Section: Discussionmentioning
confidence: 93%